2018
DOI: 10.1001/jamapsychiatry.2018.0768
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Electroconvulsive Therapy vs Pharmacotherapy/Psychotherapy for Treatment-Resistant Depression in the United States

Abstract: For US patients with treatment-resistant depression, ECT may be an effective and cost-effective treatment option. Although many factors influence the decision to proceed with ECT, these data suggest that, from a health-economic standpoint, ECT should be considered after failure of 2 or more lines of pharmacotherapy/psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 71 publications
0
70
1
10
Order By: Relevance
“…However, the mechanism of how a controlled seizure leads to reduced depressive symptoms remains poorly understood 1 . Despite popular perception that ECT is antiquated, it can be superior to medication and serves as a vital hope for remission in treatment-resistant cases of depression, bipolar disorder, suicidality and catatonia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of how a controlled seizure leads to reduced depressive symptoms remains poorly understood 1 . Despite popular perception that ECT is antiquated, it can be superior to medication and serves as a vital hope for remission in treatment-resistant cases of depression, bipolar disorder, suicidality and catatonia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…and efficacy, ECT remains a stigmatized treatment in psychiatry. 3 Previous studies have found that attitudes toward and knowledge about ECT differ among mental health professionals with more positive attitudes being associated with better knowledge. 11 Studies have found that knowledge improves with targeted education about ECT and that this results in improving attitudes toward ECT.…”
Section: Discussionmentioning
confidence: 99%
“…ECT is approved for these indications by the National Institute for Health and Care Excellence (NICE) and in international guidelines 2122. Additionally, ECT is cost effective and improves quality of life 23. In England 0.43 per 10 000 population are treated annually with ECT, and worldwide about a million people have ECT each year 2425…”
Section: No— Sameer Jauhar and Declan M Mcloughlinmentioning
confidence: 99%